Symbiotic effect of Bradyrhizobium yuanmingense isolates over Bradyrhizobium japonicum with soybean - Appunu, C; Kumar, Ravinder; Sreenivasa, V; Manjunatha, T; Mahadevaiah, C; Sasirekha, N; Prabavathy, V. R; Nair, Sudha (Legume research, 2015)
Symbiotic effect of twenty one indigenous Bradyrhizobium yuanmingense strains obtained from nodules of soybean cultivated in India was comparatively evaluated with B. japonicum ASR011 on soybean cv. JS335 for improved nodulation and plant growth performance under greenhouse conditions. Significant variation in symbiotic potential among native B. yuanmingense strains was observed and few of them exhibited significantly superior symbiotic performance i.e. improved the shoot and root dry weights and shoot N content compared to non-inoculated plants and over B. japonicum inoculated plants. The symbiotically efficient B. yuanmingense strains may have applications in the formulation of appropriate inocula to improve soybean crop yield on Indian soils.